1999
DOI: 10.1046/j.1365-2222.1999.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Do mite avoidance measures affect mite and cat airborne allergens?

Abstract: Encasing covers and hot washing of bed linen reduced mite aeroallergen (and mattress cat allergen in the absence of cats). This could mean dual benefits to a patient sensitive to both mite and cat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…However, these studies generally report that the concentration of Der p 1 in dust from mattresses and carpets in homes is much greater than the concentration of Der 2 (Der p 2 ? Der f 2 together) (Calvo et al 2005;Carswell et al 1999;Chen et al 2002;Su et al 2001;Tsay et al 2002). The relationship (ratio) between Der p 1 and Der p 2 found in our whole cultures is consistent with what is reported for dust samples taken from homes around the world.…”
Section: Discussionsupporting
confidence: 94%
“…However, these studies generally report that the concentration of Der p 1 in dust from mattresses and carpets in homes is much greater than the concentration of Der 2 (Der p 2 ? Der f 2 together) (Calvo et al 2005;Carswell et al 1999;Chen et al 2002;Su et al 2001;Tsay et al 2002). The relationship (ratio) between Der p 1 and Der p 2 found in our whole cultures is consistent with what is reported for dust samples taken from homes around the world.…”
Section: Discussionsupporting
confidence: 94%
“…292,296 In general, measures used to reduce exposure to dust mite work to some extent for cat allergen as well. 285 Some 297,298 but not all 292,296,300 studies have demonstrated reduced airborne cat allergen by washing the animal on a weekly basis. Frequent bathing of dogs (at least twice a week) similarly has been found to be effective for reducing dog allergen exposure.…”
Section: Management Of Rhinitismentioning
confidence: 99%
“…279,285 Vinyl encasings are effective, although cloth encasings with semipermeable plastic backing are more comfortable and durable. If a mattress is old, replacement should be considered, but even new hypoallergenic mattresses and pillows should be encased because mite colonization occurs within weeks.…”
Section: Management Of Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…2000), for the same reasons as discussed under ‘house dust mites’. Deep‐cleaning strategies will only work if the source of the allergen (the pet) is removed, although Fel d 1 will remain in the building for at least 6 months (Carswell et al. 1999, Boleman 2000).…”
Section: Resultsmentioning
confidence: 99%